2007
DOI: 10.1080/02841850701589308
|View full text |Cite
|
Sign up to set email alerts
|

Variations in internal iliac veins detected using multidetector computed tomography

Abstract: MDCT demonstrates six types of IIV variations; the prevalence rate of IIV anomalies is not low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 14 publications
1
20
1
Order By: Relevance
“…The anatomic variations and the congenital anomalies of these vessels have been well explained. 3 We reported a complex anatomic variation of retroperitoneal veins, which, to the best of our knowledge, has not been mentioned before in the literature. …”
mentioning
confidence: 85%
See 1 more Smart Citation
“…The anatomic variations and the congenital anomalies of these vessels have been well explained. 3 We reported a complex anatomic variation of retroperitoneal veins, which, to the best of our knowledge, has not been mentioned before in the literature. …”
mentioning
confidence: 85%
“…2 The interiliac communicating vein is considered to be originated from iliac anastomosis between posterior cardinal veins. 3 The IVC is composed of 4 segments: hepatic, suprarenal, renal, and infrarenal. The hepatic segment is derived from the vitelline vein.…”
Section: Discussionmentioning
confidence: 99%
“…Its tributaries include the gluteal, internal pudendal, obturator, lateral sacral, middle rectal, vesical, uterine, and vaginal veins (Standring 2008). Morita et al (2007) observed that the right separated internal iliac vein drained into a central right common iliac vein in 1.6% (Fig. These were more common in females, with a female/male ratio of 1.7:1.…”
Section: Internal Iliac Veinmentioning
confidence: 95%
“…The external and internal iliac veins can join at a higher level, forming a short common iliac vein (Lotz and Seeger 1982;Morita et al 2007). Formation of the left common iliac vein at a higher level was seen in 7.9% by Morita et al (2007) (Fig.…”
Section: High Junctionmentioning
confidence: 99%
See 1 more Smart Citation